ナンキョク インセキ ALH-77219 メソシデライト ノ ジキ ブンセキ - 永田, 武; ナガタ, タケシ; 船木, 實; フナキ, ミノル; Nagata, Takesi; Funaki, Minoru (1983)
P(論文) 南極隕石のコレクションのうちでは稀少な, メソシデライトALH-77219の磁気分析を行い, また, その中に含まれる金属粒の化学成分について, EPMAによる分析を行った。EPMA分析の結果, ALH-77219中の金属相は, Ni含有量5-6wt%のカマサイトおよびNi含有量約50wt%のテーナイト相とに2分される。ALH-77219の熱磁化曲線は, 平均Ni含有量6wt%のカマサイトと平均Ni含有量54wt%のテーナイトが混在し, そのテーナイト相の大部分は, テトラテーナイト規則格子構造を持つことを示す。6% Niカマサイトおよび54% Niテーナイトの含有量は, それぞれ19.3wt%および6.3wt%である。 Magnetic analyses are made on an Antarctic mesosiderite ALH-77219,and chemical analyses of metallic grains in the mesosiderite are carried out with the aid of an EPMA. The EPMA analyses show that the metallic phases in ALH-77219 are composed of kamacite of 5-6wt% Ni and taenite of about 50wt% Ni. The thermomagnetic analyses show that the mesosiderite ALH-77219 contains kamacite phase of about 6wt% Ni on average of 19.3% in weight and taenite phase of about 54wt% Ni on average of 6.3% in weight. The major parts of the taenite phase are of the superlattice structure of tetrataenite, which has a large magnetic anisotropy. departmental bulletin paper